Aerobic denitrifying bacterial-fungal consortium mediating nitrate removal: Dynamics, network patterns and interactions - Xiaotian Zuo; Wei Xu; Shiping Wei; Shuangcheng Jiang; Yu Luo; Minghuang Ling; Kai Zhang; Yuanhao Gao; Zhichao Wang; Jiege Hu; Hans-Peter Grossart; Zhuhua Luo (iScience, 2023)
Summary: In recent years, nitrogen removal by mixed microbial cultures has received increasing attention owing to cooperative metabolism. A natural bacterial-fungal consortium was isolated from mariculture, which exhibited an excellent aerobic denitrification capacity. Under aerobic conditions, nitrate removal and denitrification efficiencies were up to 100% and 44.27%, respectively. High-throughput sequencing and network analysis suggested that aerobic denitrification was potentially driven by the co-occurrence of the following bacterial and fungal genera: Vibrio, Fusarium, Gibberella, Meyerozyma, Exophiala and Pseudoalteromonas, with the dominance of Vibrio and Fusarium in bacterial and fungal communities, respectively. In addition, the isolated consortium had a high steady aerobic denitrification performance in our sub-culturing experiments. Our results provide new insights on the dynamics, network patterns and interactions of aerobic denitrifying microbial consortia with a high potential for new biotechnology applications.